2019
DOI: 10.1016/j.ebiom.2019.08.076
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the microbiome on checkpoint inhibitor treatment in patients with non-small cell lung cancer and melanoma

Abstract: The microbiome is increasingly recognized for its role in multiple aspects of cancer development and treatment, specifically in response to checkpoint inhibitors. While checkpoint inhibitors have revolutionized cancer treatment by producing durable anti-tumor responses, only a minority of patients respond to the available immunotherapy drugs and accurate, sensitive and specific microbiome predictors of response to treatment remain elusive. Additionally, the specific mechanisms linking the microbiome and host i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 54 publications
(106 reference statements)
1
28
0
3
Order By: Relevance
“…However, recent studies show that the antibiotic therapy may be associated with reduced therapeutic effects of ICI therapy. Routy et al published data suggesting that antibiotic use within 60 days before treatment initiation is associated with a negative effect on OS in a mixed cohort of NSCLC, urothelial carcinoma and RCC patients [ 41 , 102 ].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies show that the antibiotic therapy may be associated with reduced therapeutic effects of ICI therapy. Routy et al published data suggesting that antibiotic use within 60 days before treatment initiation is associated with a negative effect on OS in a mixed cohort of NSCLC, urothelial carcinoma and RCC patients [ 41 , 102 ].…”
Section: Main Textmentioning
confidence: 99%
“…In a follow-up study with a larger population of NSCLC patients, it was observed that antibiotic use within 1 month before immunotherapy was associated with a significantly worse OS [ 42 , 102 ]. These findings are consistent with other results demonstrating that broad spectrum antibiotic therapy within 2 weeks prior to or after ICI use is associated with shorter PFS and a lower response rate [ 43 , 102 ].…”
Section: Main Textmentioning
confidence: 99%
“…Several parameters influencing the probability of response to ICIs have been identified and recently reviewed elsewhere [ 5 ]. These can be subdivided into features of the tumor genome [ 6 , 7 ], host immune-related traits [ 8 ] and the microbiota [ 9 11 ]. These multiple and diverse factors shape the complex interaction of the tumor and the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…However, all patients with cancer do not respond to ICI treatment. Furthermore, recent studies have suggested that some intestinal bacteria are capable of enhancing antitumor immunity and augmenting the effect of ICIs [97][98][99]. A study using a mouse model showed that Bifidobacterium activated dendritic cells, and thereby enhanced antitumor immunity and augmented the antitumor effect of the anti-PD-L1 antibody [97].…”
Section: Effect Of Microbes On Cancer Immunotherapymentioning
confidence: 99%